THE INFLUENCE OF ORGANIZATION CULTURE AND INTERNAL AUDIT ON GOOD GOVERNANCE (Survey in Government Office of Banyumas City) - Destin Alfianika Maharani; Ika Siti Fatimah (Perwira Journal of Economics & Business, 2021)
This study aims to determine the influence of internal audit and organizational culture on the realization of good governance. The type of research methods used by the author is used by the writer is a study that is descriptive and associative. Descriptive analysis method is a research conducted to determine the value of independent variables, either one variable or more (independent) without making comparisons or connecting with other variables while associative analysis is research that aims to determine the relationship of two variables or more. Based on the results of the study note that organizational culture affects the variable good governance of 41.6% with a significance value of 0.009. Furthermore, internal audit affects good governance variable of 54.8% with a significance value of 0.002. Then organizational culture and internal audit able to explain variable good governance equal to 72%. with a significance value of 0.000.